Effect of the starch structure fermented by Lactobacillus plantarum LB-1 and yeast on rheological and thermomechanical characteristics of dough. (1st February 2022) - Sun, Lei; Sun, Xinyang; Du, Yifei; Fang, Yong; Yang, Wenjian; Hu, Qiuhui; Pei, Fei
Highlights: Structural variations of starch co-fermented by lactobacillus/yeast were revealed. Co-fermentation increased the fingerprint A-chains and crystallinity of starch. Co-fermented starch with porous structure had higher solubility and swelling power. Co-fermented starch can improve dough rheological and thermomechanical properties. Abstract: This study focused on exploring the structural variations of starch co-fermented by Lactobacillus plantarum LB-1 and yeast ( Saccharomyces cerevisiae ), and the relationship between fermented starch structure and dough characteristics. Co-fermentation resulted in the increased short chain content and crystallinity (32.07%) of starch with lower molecular weight. A higher content of fingerprint A-chains of amylopectin and fingerprint B-chains of α, β-limited dextrin in the co-fermented starch endowed dough with excellent anti-retrogradation ability. Moreover, the co-fermented starch with higher swelling power (9.44 g/g) and solubility (20.40%) had a rough and irregular structure and many gaps in the appearance, which were conducive to binding water, thus promoting high dough elasticity and strength. These results extended the knowledge of starch structure–property relationship under the microbial activities, which may be beneficial to promote better flour products.